2004
DOI: 10.1007/s10792-005-5014-4
|View full text |Cite
|
Sign up to set email alerts
|

Foveolar Choroidal Blood Flow in Idiopathic Macular Hole

Abstract: Although, it may be result of macular hole, not necessarily the cause of it, these findings suggest that the eyes with idiopathic macular hole are associated with reduced foveolar blood flow. The measurement of the foveolar blood flow from choriocapillaris may be useful for identifying the subjects who have increased risk of development of macular hole in future. The study showed the association of a decrease in foveolar choroidal blood flow in eyes with idiopathic macular hole using HRF. Authors suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
(25 reference statements)
0
11
0
1
Order By: Relevance
“…Recently, Heidelberg retinal flowmetry showed that the mean blood flow and velocity were reduced in eyes with stage 4 and stage 1a MH compared with normal eyes 26 . They have proposed that choroidal hypoperfusion may be a factor for FTMH formation because of a decrease in nutrient transport and an increase in susceptibility to damaging factors 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Heidelberg retinal flowmetry showed that the mean blood flow and velocity were reduced in eyes with stage 4 and stage 1a MH compared with normal eyes 26 . They have proposed that choroidal hypoperfusion may be a factor for FTMH formation because of a decrease in nutrient transport and an increase in susceptibility to damaging factors 26 .…”
Section: Discussionmentioning
confidence: 99%
“…They have proposed that choroidal hypoperfusion may be a factor for FTMH formation because of a decrease in nutrient transport and an increase in susceptibility to damaging factors 26 . The choroid contributes the blood supply to the outer retina, contributing to 100% blood and oxygen supply in the foveal avascular zone, where IMH occurs 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 This leads to the hypothesis that reduced vasculature, insufficient blood and oxygen supply, may increase the susceptibility of the fovea to traction. 53 Subsequent EDI-OCT reports did not confirm choroidal thinning in patients with idiopathic MH. 54…”
Section: Vitreoretinal Interface Diseasesmentioning
confidence: 98%
“…Although the cause of IMH is generally accepted to be vitreomacular traction and tangential traction of the inner limiting membrane [15], the exact pathogenic mechanisms are still elusive. In fact, other factors, as local vascular alteration, has been shown to play a role in the formation of IMH [16,17]. Additional information concerning FE conditions may improve the knowledge about IMH pathogenesis and help predict the risk of bilateral disease.…”
Section: Introductionmentioning
confidence: 99%